Gendarmerie in Hradec Králové, Introduction to Its Structure in the 1930s (Theatrum historiae, 2015)
The study tries to summarize the current knowledge of the activities of particular sections of the gendarmerie in Hradec Králové in the 1930s. The attention is paid not only to the organization of the gendarmerie, but also to its duties and circumstances under which they worked in the observed period. The organization and activity of the gendarmerie in Hradec Králové are presented in the context of the statewide events and the organization of security.
Keywords: gendarmerie; Hradec Králové; 1930s; security troops